MUSYKILATU AT-THULLAAB FII TA’LIIMI MAHARATUL KALAAM ‘INDA BARNAAMIJ SHAUTUL ‘ARAB BI JAAMI’ATI UMMUL QURO AL-ISLAMI - Muh. Abrar; Muhammad Firnanda; Emnis Anwar (SHAWTUL ARAB, 2021)
The role of the language is very important for social life to facilitate interaction in it, and the role of the Arabic language for Muslims in particular is very important, because the Arabic language is the opening key to understanding and Islamic studies from its original sources (the Qur’an and Hadith). Experimentally, the Arabic language is the language used by Arab countries and society. Islamic. This study aims to identify the problems that exist in teaching the Arabic language, especially in teaching speaking skill to Saudi students at Umm Al-Qura Islamic University, and finding solutions to overcome these problems. In this study, the researcher used the qualitative descriptive approach, which is a research method that describes in detail the results of the study. The researchers can conclude from the results of the study that: There are 3 problem formulas in this study that the researchers can deduce, namely: 1. Students' problems in learning the speaking skill in the Voice of the Arabs program at Umm Al-Qura Islamic Institute, 2. Solutions and 3. Efforts to overcome problems Students to speak Arabic. 3. Factors supporting and inhibiting the learning of speaking skill for students at Umm Al-Qura Islamic University. The research results from the formulation of the problem created a result that includes: lack of support from the closest people, lack of mastery of Arabic vocabulary, and increased awareness and activity of the officials of the Study Program Association and other students of Arabic language education playing an important role in creating an Arab environment, as well as providing a special environment for the Arabic language And human resources for students of Arabic language education, and the Umm Al-Qura campus is an Islamic campus that is the main supporter of students who should be more active in Arabic